PELATIHAN BAHASA INGGRIS MENGGUNAKAN MEDIA GAMBAR BAGI SISWA SEKOLAH DASAR DI KECAMATAN RINDI - SUMBA TIMUR - Malo, Raynesta Mikaela Indri; Kapoe, Suryani Kurniawi K. L.; Koro, Januard Alberto; Beba, Ayu Asari Rambu; Jawa, Marheni Putri (Kumawula: Jurnal Pengabdian Kepada Masyarakat, 2024)
As an international language, English is a crucial subject for students from primary to secondary levels. However, due to various existing obstacles and curriculum regulations, many schools in East Sumba cannot provide English as part of the learning process at school. For this reason, this community service activity (PkM) is aimed at introducing and teaching simple English to students using images with various topics that are familiar to students' daily lives. This activity was carried out at 2 partner schools, namely SDN Hanggaroru and SDN Lailanjang. There were 4 stages of implementing this activity, the pre-test of students' basic English skills, design of image media, the training program, and the post-test of students' English skills after training. The achievement of this activity is the availability of 1 series of English learning picture media consisting of 9 pictures including numbers, names of days, names of months, names of vegetables, names of fruit, names of livestock, names of wild animals, school necessities, and daily necessities. From the results of the pre-test conducted before the training and the post-test conducted after the training, it was found that there was an increase in English language skills of 78.9% for the students of SDN Hanggaroru and 56.1% for the students of SDN Lailanjang. This shows that the use of image media as a tool for the learning process has been proven to encourage students to remember and understand English vocabulary more quickly. This is possible because the use of images directly influences children's visuals so that they see what they are learning as something interesting which ultimately helps them in mastering vocabulary.Sebagai salah satu bahasa internasional, Bahasa Inggris sangat penting untuk dipelajari oleh siswa sekolah dari level sekolah dasar hingga menengah. Akan tetapi, karena berbagai hambatan yang ada serta aturan kurikulum, banyak sekolah di Sumba Timur yang tidak dapat menyediakan Bahasa Inggris sebagai bagian dari proses pembelajaran di sekolah. Untuk itu, kegiatan pengabdian kepada masyarakat (PkM) ini ditujukan untuk memperkenalkan dan mengajarkan Bahasa Inggris sederhana kepada siswa menggunakan media gambar dengan berbagai topik yang akrab dengan kehidupan sehari-hari siswa. Kegiatan ini dilaksanakan di 2 sekolah mitra yaitu di SDN Hanggaroru dan SDN Lailanjang. Terdapat 4 tahap pelaksanaan PkM ini yaitu pre-test kemampuan dasar Bahasa Inggris siswa, perancangan media gambar, pelatihan, dan post-test kemampuan Bahasa Inggris siswa setelah pelatihan. Capaian kegiatan ini adalah tersedianya 1 seri media gambar belajar Bahasa Inggris yang terdiri dari 9 gambar meliputi angka, nama-nama hari, nama-nama bulan, nama-nama sayuran, nama-nama buah, nama-nama ternak, nama-nama hewan non ternak, barang kebutuhan sekolah, dan barang kebutuhan sehari-hari. Dari hasil pre-test yang dilakukan sebelum pelatihan dan post-test yang dilakukan setelah pelatihan, ditemukan bahwa terdapat peningkatan kemampuan Bahasa Inggris sebesar 78,9% untuk siswa SDN Hanggaroru dan 56,1% untuk siswa SDN Lailanjang. Hal ini menunjukkan bahwa penggunaan media gambar sebagai alat bantu proses pembelajaran, terbukti dapat mendorong siswa dalam mengingat dan memahami kosakata Bahasa Inggris dengan lebih cepat. Hal ini dimungkinkan karena penggunaan media secara langsung mempengaruhi visual anak sehingga melihat hal yang dipelajari sebagai sesuatu yang menarik yang pada akhirnya membantu mereka dalam penguasaan kosakata.